Time, intensity of detasseling rainfed maize (Zea mays) for improving productivity, economics and rainwater-use efficiency - SAMMAURIA, R; BALYAN, J K; BAIRWA, P C (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted in factorial RBD with three replications during kharif, 2010–2012 at Bhilwara, India to study the effect of time and intensity of detassling of rainfed maize on its productivity, economics and rainwater use efficiency. Maize was detassled for 3 time series namely Just after emergence (JAE), 3 Days after emergence (3 DAE) and 7 Days after emergence (7 DAE) and for 4 intensities such as 25, 50, 75 and 100% removal. Detassling had strong positive effect on productivity and economics, particularly during moisture stress situations, suggesting that detasseling is beneficial. Detasseling 7 DAE increased the grain and yield by 22, 9 and 12% in comparison to detasseling JAE during 2010, 2011 and 2012, respectively. The respective figures for these three years for detasseling at 3 DAE were 15, 6 and 10%. Among the intensities, tassel removal up to 50% was the most effective in improving yield characters and yields during all three years and was economically viable. The higher net return and B:C ratio were recorded with detasseling 7DAE. The 50% tassels removal gave the highest net returns. The factor productivity and rainwater use efficiency also improved by various treatments. Detasseling was highly sustainable for physical production and moderately sustainable for viable sustainable Index.